2021
DOI: 10.3390/jof7090692
|View full text |Cite
|
Sign up to set email alerts
|

Safety Evaluation of Fungal Pigments for Food Applications

Abstract: Pigments play a major role in many industries. Natural colors are usually much safer when compared to synthetic colors and may even possess some medicinal benefits. Synthetic colors are economical and can easily be produced compared to natural colors. In addition, raw plant materials for natural colors are limited and season dependent. Microorganisms provide an alternative source for natural colors and, among them, fungi provide a wide range of natural colorants that could easily be produced cheaply and with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 83 publications
0
16
0
Order By: Relevance
“…As secondary metabolites, these polyketide-based pigments exhibit a wide range of biological activities, such as antimicrobial, antifungal, antiviral, antioxidant, cytotoxic, nematicidal, anti-inflammatory, and anti-tumoral activities, among other useful therapeutic applications [ 39 , 40 , 41 , 42 ]. However, considering that some Penicillium and Talaromyces species, including T. wortmanni , are known to produce different mycotoxins [ 43 , 44 ], and that some can be co-produced along with pigments, it is necessary to perform a safety evaluation during the bioprocess before being used at the industrial scale, as well as the structural identification of the products [ 12 ]. For example, the potential of Talaromyces purpurogenus to produce pigments at the industrial scale has been discouraged due to the risk of mycotoxin production; Talaromyces atroroseus is able to produce pigments without any co-production of mycotoxins, thus, this species is highly recommended for industrial purposes [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As secondary metabolites, these polyketide-based pigments exhibit a wide range of biological activities, such as antimicrobial, antifungal, antiviral, antioxidant, cytotoxic, nematicidal, anti-inflammatory, and anti-tumoral activities, among other useful therapeutic applications [ 39 , 40 , 41 , 42 ]. However, considering that some Penicillium and Talaromyces species, including T. wortmanni , are known to produce different mycotoxins [ 43 , 44 ], and that some can be co-produced along with pigments, it is necessary to perform a safety evaluation during the bioprocess before being used at the industrial scale, as well as the structural identification of the products [ 12 ]. For example, the potential of Talaromyces purpurogenus to produce pigments at the industrial scale has been discouraged due to the risk of mycotoxin production; Talaromyces atroroseus is able to produce pigments without any co-production of mycotoxins, thus, this species is highly recommended for industrial purposes [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Particularly, fungi are known as producers of a wide range of pigments that include carotenoids, melanins, flavins, phenazines, quinones, and, more specifically, monascins and violacein, or indigo [ 8 , 11 , 12 , 13 , 14 ]. Fungal genera such as Aspergillus , Fusarium , Penicillium, Monascus , Trichoderma , and Laetiporus produce those and many other pigments used to obtain colors such as red, purple, yellow, brown, orange, and green with wide industrial applications [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Though, many other microbial strains especially fungal sp. exhibit potential as food colorants but requires to be subjected to extensive toxicity and quality tests before being approved by regulatory food authorities for commercial usage ( Dufossé, 2018a ; Chatragadda and Dufossé, 2021 ; Poorniammal et al, 2021 ). The market potential of anthraquinone and azaphilone-producing strains such as Talaromyces sp., Penicillium sp.…”
Section: Multifaceted Applications Of Microbial Color Palettesmentioning
confidence: 99%
“…along with toxin-free production of Monascus sp. pigments for food-grade colorations has been highlighted by various studies ( Dufossé, 2018b ; He et al, 2021 ; Poorniammal et al, 2021 ). Apart from human consumption, the carotenoid pigments have high demand as food additives for animals or aquatic organisms ( Meléndez-Martínez et al, 2020 ; Pereira da Costa and Campos Miranda-Filho, 2020 ).…”
Section: Multifaceted Applications Of Microbial Color Palettesmentioning
confidence: 99%
“…It is commonly reported that pigments are considered safe, non-toxic, non-carcinogenic, biodegradable, and of low risk to the environment (Wrolstad and Culver, 2012;Dikshit and Tallapragada, 2018) as they do not interfere with the aquatic biota, not showing an undesirable/harmful tendency toward allergic reactions, intolerances, in addition to other effects such as mutagenicity and potential carcinogenic effect (Dikshit and Tallapragada, 2018;Aman Mohammadi et al, 2022). However, like any other product available for use, natural pigments need to be extensively studied for toxicity and safety (Kobylewski and Jacobson, 2012), as several other widely used components have been banned due to proven adverse effects, including synthetic dyes such as ponceau, tartrazine, and sunset yellow, for example (Kobylewski and Jacobson, 2012;Poorniammal et al, 2021). Additionally, is important to emphasize that legal aspects related to doses and approval of natural pigments use are important for feasibility and safety of use (Commission Regulation, 2014).…”
mentioning
confidence: 99%